“Молода Україна” Олени Пчілки та її погляди на проблеми дитячого читання - Новаківська, Л.В (Інститут літератури ім. Т.Г. Шевченка НАН України, 2009)
В статье рассматриваются взгляды Олены Пчилки – украинской писательницы, ученого, педагога – на проблемы детской литературы и детского чтения. The article reveals the ideas of the famous Ukrainian writer, educationist and teacher – Olena Pchilka – of the problems of literature and children reading.